Correlation between Modified Clinical Pulmonary Infection Score with Duration of Mechanical Ventilation of Pneumonia Patient in ICU Cipto Mangunkusumo Hospital - Madjid, Amir S; Sugiarto, Adhrie; Putri, Regina Prima; Alatas, Anas (Perdatin Pusat, 2015)
Current extubation parameters are not entirely accurate. Therefore, weaning from mechanical ventilation is difficult, especially in pneumonia patient. One of scoring system for evaluation of pneumonia patient is modified clinical pulmonary infection score (MCPIS). This score evaluates temperature, leucocyte count and differential count, volume and consistency tracheal secretion, oxygenation and chest x-ray. This study aimed to estimate the correlation between MCPIS score with duration of mechanical ventilation of pneumonia patient in ICU Cipto Mangunkusumo Hospital. This was a prospective cohort study among pneumonia patients with mechanical ventilation at ICU Cipto Mangunkusumo Hospital from October 2014 to February 2015. MCPIS were measured at the point of admission and 72 hours after admission. Date of extubation was recorded to determine the duration of mechanical ventilation. There were 48 subjects included in this study. Early MCPIS score (median 6) was higher than MCPIS score after 72 hours (median 5) with mechanical ventilation duration 3-19 days (median 7). There was no significant correlation between early MCPIS score with mechanical ventilation duration (p=0,180; r=0,197). There was significant moderate correlation between MCPIS score after 72 hours with mechanical ventilation duration (p=0,000; r=0,539). This study concluded there was significant correlation between MCPIS after 72 hours with mechanical ventilation duration in pneumonia patients in ICU.